Isolation of the crude oil degrading marine Acinetobacter sp. E11 - Razak, C.N.A.; Wang, W.F.; Rahman, S.H.S.A.; Basri, M.; Salleh, A.B. (Wiley-VCH Verlag Berlin GmbH, 1999)
The Acinetobacter sp. E11, isolated from Port Dickson Beach, Malaysia, was able to grow in media containing crude oil as the sole carbon and energy source. Substrate specificity studies showed that the bacterium exhibited substrate preference as growth was observed only in media containing aliphatic hydrocarbons, while aromatic and cyclic hydrocarbons inhibited growth. With the aliphatic hydrocarbons, growth was seen only in the long-chain alkanes tested (pentadecane, dodecane and hexadecane). No growth was recorded in the short-chain alkanes (pentane, hexane and heptane) tested. With complex hydrocarbons, only crude oil and 4T SHELL engine oil supported growth. No growth was observed in kerosene and PETRONAS gasoline. The isolate could grow in up to 10% and 20% [v/v] of the crude oil and alkanes tested, respectively. Among the long-chain alkanes tested, hexadecane was the most preferred, followed by pentadecane and dodecane. Nitrogen and phosphorous supplements were essential for growth and the best growth was achieved with 3% nitrogen/phosphorous additions. Microscopic observation revealed that the bacterium adhered to the hexadecane and crude oil droplets. GC analysis showed that the bacterium was able to degrade more than 60% of the hydrocarbons in the crude oil in 15 days at 37°C compared to the uninoculated media.